HER2-LAMP vaccines effectively traffic to endolysosomal compartments and generate enhanced polyfunctional T cell responses that induce complete tumor regression. Issue 1 (12th June 2020) - Chen, Alan Chen; Xu, Renhuan; Wang, Tao; Wei, Junping; Yang, Xiao-Yi; Liu, Cong-Xiao; Lei, Gangjun; Lyerly, Herbert Kim; Heiland, Teri; Hartman, Zachary Conrad
Abstract : Background: The advent of immune checkpoint blockade antibodies has demonstrated that effective mobilization of T cell responses can cause tumor regression of metastatic cancers, although these responses are heterogeneous and restricted to certain histologic types of cancer. To enhance these responses, there has been renewed emphasis in developing effective cancer-specific vaccines to stimulate and direct T cell immunity to important oncologic targets, such as the oncogene human epidermal growth factor receptor 2 (HER2), expressed in ~20% of breast cancers (BCs). Methods: In our study, we explored the use of alternative antigen trafficking through use of a lysosome-associated membrane protein 1 (LAMP) domain to enhance vaccine efficacy against HER2 and other model antigens in both in vitro and in vivo studies. Results: We found that inclusion of this domain in plasmid vaccines effectively trafficked antigens to endolysosomal compartments, resulting in enhanced major histocompatibility complex (MHC) class I and II presentation. Additionally, this augmented the expansion/activation of antigen-specific CD4+ and CD8+ T cells and also led to elevated levels of antigen-specific polyfunctional CD8+ T cells. Significantly, vaccination with HER2-LAMP produced tumor regression in ~30% of vaccinated mice with established tumors in an endogenous model of metastatic HER2+ BC, compared with 0% of HER2-WT vaccinated mice. This therapeutic benefit is associated with enhanced tumor infiltration of activated CD4+ and CD8+ T cells. Conclusions: These data demonstrate the potential of using LAMP-based endolysosomal trafficking as a means to augment the generation of polyfunctional, antigen-specific T cells in order to improve antitumor therapeutic responses using cancer antigen vaccines.